Booklet Efforts to Improve Health Cadres' Knowledge about the Quality of Life of People with Diabetes Mellitus through Booklets - Wijayanti, Anisa Catur; Puspita, Widya Galih; Pratiwi, Septiani Cipta; Sahda, Renaya Amelia; Wijaya, Chayanita Sekar (Journal of Community Services and Engagement: Voice of Community (VOC), 2025)
This community service aimed to enhance the knowledge of health cadres on improving the quality of life of diabetes mellitus (DM) patients in the Kratonan Community Health Center area, Surakarta City, based on research identifying poor quality of life among some DM patients. The activities involved 16 health cadres and were conducted in three stages: planning, implementation, and evaluation. During implementation, cadres received educational booklets covering DM risk factors, complications, prevention efforts, and quality of life improvement, followed by pre-test, material presentation, discussion, and post-test sessions. Results showed an increase in average knowledge scores from 6.31 (pre-test) to 10.06 (post-test), indicating improved understanding among cadres. This intervention highlights the important role of health cadres in providing health information and psychological support to DM patients. Ongoing monitoring and evaluation of behavior changes linked to gained knowledge are recommended.